Pengaruh Pancaran Radio Komunikasi Bali Radar Terhadap Pelayanan Lalu Lintas Penerbangan - Hidayatulloh. S, Muhammad Ihsan Taufiq; Praptiningsih, Nunuk (Politeknik Penerbangan Indonesia Curug, 2024)
The aviation communication system is very important for aviation, especially for pilots and air traffic controllers. The communication system for air traffic controllers and pilots must be adequate in order to create good communication and prevent misunderstandings between pilots and air traffic controllers. Meanwhile, the communication system at the Bali Radar APP/TMA unit cannot cover all of its areas of responsibility and is feared to affect the quality of air traffic services. After coordinating with the technical unit, the authors suggest installing a device that can extend a radio frequency signal called VHF ER (extender range), and specifically for the northern area of Mount Agung which is usually passed by VFR aircraft where the area is a class G airspace, the authors suggest creating a frequency called TIBA (Traffic Information Broadcast by Aircraft).